Traversées, hybridations grotesques et inquiétante étrangeté dans The Island of Dr Moreau (1896) de H. G. Wells : la mort de l’humain ? - Françoise DUPEYRON-LAFAY (E-REA)
Edward Prendick, the protagonist and narrator of The Island of Dr Moreau, embarks on a hazardous and terrifying crossing (between England and an unknown Pacific island) that will lead to other types of crossings – biological, taxonomical, psychological, ontological and generic ones. They will irretrievably make him a stranger to himself. Wells’s evolutionist work, like Dr Moreau’s laboratory, actually explores the problematic concepts of civilization and humanity and shows how permeable the frontiers between humans and animals are and how they insidiously dissolve, so that the humanization of animals (by Moreau) is paralleled by the (spontaneous) animalization of humans, a darkly disturbing form of regression that represents the return of the repressed, and one of the modalities of the Freudian unheimlich. Biological and ontological hybridity goes along with literary hybridity in this angst-ridden narrative that fuses science, realism and the fantastic, collapsing binary oppositions and resting on an ever-shifting in-between, grotesque logic. The island on which Prendick is compelled to live for months, instead of leading to (re)construction as in traditional utopias, is an anarchic tropical jungle that deconstructs and shatters all his norms and certainties, reflecting his wild and alien(ated) state.